Nature's music : the science of birdsong - Marler, Peter; Slabbekoorn, Hans Willem, 1967- (Elsevier Academic, 2004)
The voices of birds have always been a source of fascination. Natures Music brings together some of the worlds experts on birdsong, to review the advances that have taken place in our understanding of how and why birds sing, what their songs and calls mean, and how they have evolved. All contributors have strived to speak, not only to fellow experts, but also to the general reader. The result is a book of readable science, richly illustrated with recordings and pictures of the sounds of birds. Bird song is much more than just one behaviour of a single, particular group of organisms. It is a model for the study of a wide variety of animal behaviour systems, ecological, evolutionary and neurobiological. Bird song sits at the intersection of breeding, social and cognitive behaviour and ecology. As such interest in this book will extend far beyond the purely ornithological - to behavioural ecologists psychologists and neurobiologists of all kinds. * The scoop on local dialects in birdsong * How birdsongs are used for fighting and flirting * The writers are all international authorities on their subject.